2011
DOI: 10.1080/15363759.2011.559874
|View full text |Cite
|
Sign up to set email alerts
|

Gender Trends in Senior-Level Leadership: A 12-Year Analysis of the CCCU U.S. Member Institutions

Abstract: This article documents the continued gender disparities evident across U.S. higher education. While more women than men attend college and now obtain the majority of undergraduate, master's, and doctoral degrees, women continue to be underrepresented in senior-level institutional leadership roles. This phenomenon is particularly evident among the member institutions of the Council for Christian Colleges & Universities (CCCU). Given that the CCCU's 108 U.S. member campuses serve a collective student body that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Whereas women hold 26% of U.S. college presidencies (American Council on Education, 2012), only six of the 118 CCCU member institutions (i.e., 5%) have female presidents (Porterfield, 2013). Within this same institutional membership, research by Longman and Lafreniere (2012) identified that although the majority (60%) of students attending CCCU institutions are female, the male-female ratio on senior-level leadership teams as of 2010 averaged 4.99 men to .99 women (Longman & Anderson, 2011).…”
Section: Leadership Demographicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas women hold 26% of U.S. college presidencies (American Council on Education, 2012), only six of the 118 CCCU member institutions (i.e., 5%) have female presidents (Porterfield, 2013). Within this same institutional membership, research by Longman and Lafreniere (2012) identified that although the majority (60%) of students attending CCCU institutions are female, the male-female ratio on senior-level leadership teams as of 2010 averaged 4.99 men to .99 women (Longman & Anderson, 2011).…”
Section: Leadership Demographicsmentioning
confidence: 97%
“…Given the disparity between the demographics of the student population across CCCU institutions (60% female) and the average composition (17% female) of the senior leadership teams (Longman & Anderson, 2011), it is important to better understand the organizational culture of these institutions as well as the motivators, encouragers, and discouragers for women to move into leadership roles. This study was guided by the research question: What factors affect women's decisions about higher levels of positional leadership in Christian higher education?…”
Section: Factors Influencing Women's Leadership Aspirationsmentioning
confidence: 99%
“…In 2010, only six of 110 presidents were female, with the two most recent additions only in the 2009-2010 academic year. Given that the role of chief academic officer is the primary pathway to the presidency, it is notable that as of 2010, only 18 female chief academic officers in the CCCU were women (Longman & Anderson, in press). Trends in CCCU senior-level leadership from 1998 to 2010, analyzed by Longman and Anderson, documented that as of 2010, the average number of individuals serving in vice presidential roles or higher across the 108 U.S. member institutions was 4.9 men and .99 women; the percentage of institutions with no women in such executive positions was 33% (36 institutions) while the percentage with one woman in executive leadership was 44% (48 institutions).…”
Section: Leadership Within Faith-based Higher Educationmentioning
confidence: 99%
“…The classroom and workplace climate at higher education institutions continues to be tense in many cases (Glazer-Raymo, 1999;Hall & Sandler, 1982;Sandler, 1997;Sandler et al, 1996). Recent research indicates that institutional sexism at colleges and universities is an ongoing problem (Ashlee et al, 2017;Diehl & Dzbunski, 2016;Fernandez et al, 2006;Lipton, 2015;Longman & Anderson, 2011;Ramirez, 2017;Savigny, 2014;Vaccaro, 2010;White et al, 2010). Vaccaro (2010) found that women in higher education, both students and employees, would like to have meaningful conversation about diversity while men in higher education, students and employees, are indifferent or hostile toward diversity initiatives.…”
Section: Higher Education Climatementioning
confidence: 99%
“…White et al (2010) concluded that higher education senior administration continues to be a career path dominated by men and a major disadvantage for women in Europe. Longman and Anderson (2011) focused their research on gender trends as related to the Council for Christian Colleges & Universities (CCCU) in the United States. With a total of 108 institutions in the United States and a student body comprised of 60%…”
Section: Higher Education Climatementioning
confidence: 99%